2015
DOI: 10.1002/2015jd023884
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐polarization radar signatures in snowstorms: Role of snowflake aggregation

Abstract: In this article a potential role of snowflake growth by aggregation on formation of dual‐polarization radar signatures in winter storms is discussed. We advocate that the observed bands of increased values of specific differential phase (Kdp) can be linked to the onset of aggregation. These bands are caused by high number concentrations of oblate relatively dense ice particles and take place in regions where an ice phase “seeder‐feeder” is active. On the other hand, the differential reflectivity (Zdr) bands, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
118
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(135 citation statements)
references
References 44 publications
13
118
0
Order By: Relevance
“…Z DR and K DP depressions aloft associated with increases in Z H and ρ HV above the ML suggest increases of ice particle mean sizes due to riming and/or aggregation. Recently, Moisseev et al (2015) argued that the processes responsible for enhanced K DP -and Z DRbands might be different: they advocated that the K DP bands are caused by high number concentrations of oblate relatively dense ice particles (early aggregates) and are linked to the onset of aggregation processes, while Z DR bands in the absence of K DP bands are observed when crystal growth is the dominant snow growth mechanism and the number concentration is lower. Following their arguments, it can also be speculated that aggregation processes are ongoing near the end of the observation period shown in Fig.…”
Section: Case 3: Riming/aggregation Processes Observed By Juxpolmentioning
confidence: 99%
“…Z DR and K DP depressions aloft associated with increases in Z H and ρ HV above the ML suggest increases of ice particle mean sizes due to riming and/or aggregation. Recently, Moisseev et al (2015) argued that the processes responsible for enhanced K DP -and Z DRbands might be different: they advocated that the K DP bands are caused by high number concentrations of oblate relatively dense ice particles (early aggregates) and are linked to the onset of aggregation processes, while Z DR bands in the absence of K DP bands are observed when crystal growth is the dominant snow growth mechanism and the number concentration is lower. Following their arguments, it can also be speculated that aggregation processes are ongoing near the end of the observation period shown in Fig.…”
Section: Case 3: Riming/aggregation Processes Observed By Juxpolmentioning
confidence: 99%
“…Bands of enhanced Z DR are an indicator for the generation and growth of pristine ice particles, mainly dendrites or hexagonal plates (Bader et al, 1987;Kennedy and Rutledge, 2011;Moisseev et al, 2015). However, the visible polarimetric signatures in the radar measurements in Case 2 are caused most likely by newly generated ice needles or columns.…”
Section: Case 1: Aggregation Of Needles 10:09-10:18 Utcmentioning
confidence: 99%
“…The decrease of the differential reflectivity signatures depends strongly on the aggregated pristine particle type. Moisseev et al (2015) suggested that early aggregates of dendrites align horizontally and therefore can also contribute to a high Z DR -signature. This leads to a less strong decrease of polarimetric signatures of Z DR with increasing size of the grown aggregates.…”
Section: Ice Particle Growth Processesmentioning
confidence: 99%
See 2 more Smart Citations